The impact of household food gardens on food security in South Africa, Lesotho and Zimbabwe - Fouche, Michelle Shannon (University of the Free State, 2018)
Food insecurity is a challenge faced by many in the developing world, where more and more individuals are finding healthy food inaccessible due to poverty. The triple burden of malnutrition includes undernutrition (underweight, stunting and wasting); overnutrition (overweight and obesity); and micronutrient deficiencies. These may coexist in the same household. Although it is well accepted that household food gardens have the potential to address the various forms of malnutrition, studies to confirm their impact are lacking. In the present study, a pre- and post- test study design was applied to determine the impact of household vegetable gardening interventions in South Africa, Lesotho and Zimbabwe. In each country the household food gardening intervention was implemented by a different organisation, including The Department of Agriculture in South Africa, the Society of Women against AIDS in Africa (SWAALES) in Lesotho and Batani HIV/AIDS Service organisation (BHASO) in Zimbabwe). Programme beneficiaries of these intervention partners were eligible to be included in the study. These intervention partners worked in the study population that included households from Rampepe Village in Lesotho, Kayelisha Informal Settlement in Bloemfontein and Mashvingu in Zimbabwe. In each of these areas, 50 households were purposively selected for the study in each country (for logistic reasons). From each list of 50 households, 25 households were randomly included in an intervention group and 25 were included in a control group. A standardised questionnaire was completed by fieldworkers in a structured interview with a member of the household (preferably the household head). This was done before and after the household food garden interventions. The questionnaire was used to determine socio-demographic conditions as well as indirect measures of food security in each household, using the Living Poverty Index (LPI); Months of Adequate household Food Provisioning (MAHFP); Household Dietary Diversity (HDD) and frequency of vegetables eaten. The LPI assesses the frequency that households go without basic necessities of life (namely food, water, medicine, electricity, and fuel and cash income). Responses to questions are combined to calculate a LPI score for the household, with 0 indicating no poverty to 4 (complete poverty). The MAHFP determines the total number of months out of the previous 12 months that the household was unable to meet their food needs, ranging from 0 to 12. A score of 12 indicates that the household had year-round adequate food provisioning, while 8-11 indicates moderate food security, 4-7 low food security and zero to 3 severe food insecurity. HDD is determined using the previous 24-hour period as a reference. The number of different food groups consumed during this period from a possible 12 food groups is noted. The HDD scores are interpreted in the following way: 0- 3 = low dietary diversity; 4-5 = medium dietary diversity and 6-12 = high dietary diversity. Frequency of vegetables eaten by adults and children in the households is measured using a set of 6 responses to the question ‘How frequently do ADULTS/CHILDREN in the household eat vegetables? The responses include several times a day, once a day, a times per week, once a week, rarely and Never. The sample included in the study in South Africa consisted of more female than male participants. Most participants were unmarried and more than 40% had completed high school or had a tertiary qualification. As evidenced by the LPI of 2.8, the sample was characterised by high levels of poverty. Measures of food security showed that about a third of participants had a low level of food security. At baseline, the median HDDS was 7 in the control group and 6 in the intervention group, indicating high dietary diversity. As far as frequency of vegetables consumed was concerned, less than half of participants reported that both adults and children ate vegetables relatively frequently. In terms of the impact of the intervention, the MAHFP increased to a score of 11 in the control group at follow-up and improved by 2 points in the intervention group that was exposed to the household food garden intervention. Median HDDS did not change in the control group but showed a 2 point improvement in the intervention group at follow-up. The main outcome of the intervention was obviously related to vegetable consumption, but households showed little improvement. More adults consumed vegetables a few times a day, but children’s’ vegetable consumption remained the same. Overall, the household food garden intervention had a moderately positive effect on the indicators of food security in the intervention group. An improvement in the median MAHFP from 8 to 10 occurred (95% CI for the change [-2; 0]). The sample included in the current study in Lesotho consisted of more male than female participants. About half were married and less than 20% had completed high school or had a tertiary qualification. As evidenced by the LPI of 2.5, the sample was characterised by high levels of poverty. Despite this, some measures of food security showed that participants were not as badly off as one would have expected. Even before intervention, the median MAHFP was 11 in the control group and 10 in the intervention group, indicating relatively good levels of food provisioning. At baseline, the median HDDS was 5 in the control group and 6 in the intervention group, indicating medium to high dietary diversity. As far as frequency of vegetables consumed was concerned, a relatively high percentage of participants reported that both adults and children ate vegetables relatively frequently. The habit of sharing that has been described in the Lesotho population, probably contributed to these findings. No improvements were noted in the frequency of vegetables consumed in the intervention group or in the control group. In terms of the impact of the intervention, the MAHFP remained at 11 in the control group at follow-up and improved by one point in the intervention group that was exposed to the household food garden intervention. Median HDDS did not change in either group at followup. The main outcome of the success of the intervention was obviously related to vegetable consumption. Significant improvements were noted in the frequency of vegetables consumed in the intervention group that were not noted in the control group. These can thus most probably be attributed to the intervention. The sample included in the current study in Zimbabwe consisted of more female than male participants. Most of the population was married and had a fairly high level of education with more than 50% of individuals having completed high school and in possession of a tertiary qualification. As evidenced by the LPI of 2.3, the sample was characterised by high levels of poverty. Despite this, some measures of food security showed that participants were not as badly off as one would have expected. Even before intervention, the median MAHFP was 11 at baseline in the control group and 10 in the intervention group, indicating relatively good levels of food provisioning. At baseline, the median HDDS was 6 in the control group and 7 in the intervention group, indicating medium to high dietary diversity. As far as frequency of vegetables consumed was concerned, a relatively high percentage of participants reported that adults ate vegetables frequently, though less frequent than in adults children still had a relatively high level of vegetable consumption. In terms of the impact of the intervention, the MAHFP improved by one point in in the control group at follow-up and remained at 11 the intervention group that was exposed to the household food garden intervention. Median HDDS did not change in either group at follow-up. The main outcome of the intervention was obviously related to vegetable consumption, but due to an already high level of consumption at baseline no significant improvement could be seen. In conclusion, the impact of the household food garden intervention varied in each of the countries. This could be attributable to different levels of education, cultures and environmental factors. The improvements that were noted do however show that food gardens have the potential to improve availability of food, level of diversity in the diet and frequency of vegetables eaten.

Voedselonsekerheid is ‘n uitdaging wat menigte mense affekteer in ontwikkelende lande, meer en meer individue bevind gesonde voedsel ontoegnklik a.g.v. armoede. Die tripel las van wanvoeding behels wanvoeding (ondermass, groei-inkorting en uittering); oormassa en vetsug; en mikrovoedingstof-tekorte en kan dikwels in die selfde huishouding gesien word. In die huidige studie, was ‘n voor- en na- toets studie ontwerp toegepas om die impak van ‘n huishoudelike groentetuin intervensie in Suid-Afrika, Lesotho and Zimbabwe te bepaal. In elke land was die huishoudelike groentetuin intervensie deur verskillende organisasies geimplementeer, die Departement van Landbou in Suid-Afrika, ‘the Society of Women against AIDS in Africa (SWAALES) in Lesotho en ‘Batani HIV/AIDS Service Organisation (BHASO)’ in Zimbabwe. Die intervensie Vennote se begunstigdes het in aanmerking gekom vir die studie. Die intervensie Vennote het in die studie bevolking gewerk en dit het Kayelisha informele nedersetting in Bleomfontein, Rampepe dorpie in Lesotho en Mashvingu in Zimbabwe ingesluit. 50 huishoudings in elk van die gebiede was uitgesonder vir die studie in elke land (vir logistieke redes). Van elke lys van 50 huishoudings is daar 25 huishoudings lukraak gekies vir ‘n intervensie groep en 25 was dan in n kontrole groep. ‘n Gestandardiseerde vraelys was deur veldwerkers voltooi tydens ‘n gestruktureerde onderhoud met ‘n lid van die huishouding (verkieslik die hoof). Hierdie is voor en na die huishoudelike groentetuin intervensie gedoen. The vraelys was gebruik om sosiodemografiese toestande, asook indirekte maatreëls van voedselsekerheid in elke huishouding te bepaal. Dit is gedoen d.m.v. die ‘Living Poverty Index (LPI); Months of Adequate household Food Provisioning (MAHFP); Household Dietary Diversity (HDD); en frekwensie van groenteinname. Die LPI assesseer hoe gereeld huishoudings sonder basiese noodsaaklikhede vir oorlewing gaan (naamlik kos, water, medisyne, elektrisiteit, brandstof en kontank). Reaksies op die vra is gkombineer om ‘n LPI-telling uit te werk, 0 dui geen aarmoede aan waar 4 volledige aarmoede aandui. Die MAHFP bepaal die totale aantal maande in die vorige jaar wat die huishouding nie in staat was om hulle voedsel-behoeftes te bereik nie, met ‘n omvang van 0 tot 12. A telling van 12 dui daarop aan dat die huishouding vir die hele jaar voldoende voedsel voorsiening gehad het, terwyl ‘n telling tussen 8 en 11 matige voedselsekerheid aangedui het, 4 tot 7 ‘n lae vlak van voedselsekerheid en 0 tot 3 voedselonsekerheid aangedui het. HDD word bepaal deur deurom die vorige 24 uur as ‘n verwysing te gebruik. Die aantal verskillende voedselgroepe wat tydens hierdie tydperk verorber was (uit ‘n moontlike 12 groepe) word aangeteken. Die HDD tellings word as volg interpreter: 0-3 ‘low dietary diversity’; 4-5’ medium dietary diversity’; 6-12 ‘high dietary diversity’. Frekwensie van groenteinname in volwassenes en kinders was bepaal deur 6 moontlik antwoorde of die volgende vraag ‘Hoe gereeld eet Volwassenes/Kinders indie huishouding groente? Die moontlike antwoorde sluit verskeie keer per dag, een maal per dag, ‘n paar keer ‘n week, enn maal per week, skaars en nooit in. Die monster wat tydens die studie ingesluit is vir Suid-Afrika het meer vrouens as mans bevat. Die mederheid van die deelnemers was ongetroud en meer as 40% het hoerskool voltooi of ‘n tersiere kwalifikasie besit. Die LPI in die groep (2.8) het aangedui dat die huishoudings hoe vlakke van armoede beleef. Maatreels van voedselsekerheid het gewys dat omtrent ‘n derde van die deelnemers ‘n lae vlak van voedselsekerheid handaf het. Voor die intervensie (basislyn) was die HDD median telling van die kontrole groep 7 en die intervensie groep 6, dus het die huidhoudings ‘n hoe vlak van diversiteit in hulle dieet. I.v.m. frekwensie van groenteinname, het minder as helfde van die deelnemers rapporteur dat volwasssenes en kinders op ‘n relatiewe gereelde basis groente eet. t.o.v. die impak wat die intervensie gemaak het, die MAHFP telling het verhoog na 11 in die kontrole groep met die opvolg besoek en het met 1 punte verbeter in die intervensie groep. Median HDD telling het geen veranderingin die kontrole groep getoon nie, maar het wel met 2 punte in die intervensie groep verbeter. Die hoof uitkomste van hierdie studie was duidelik om die verwantskap tussen groente tuine en groenteinname te bepaal, maar huishoudings het min verbetering gewys. Meer volwassenes het groente 1 maal per day geeet, waar kinders dieselfde hoeveelheid groente geeet het voor en na die intervensie. Oor die algemeen, het huishoudelike groentetuin intervensie n matige positiewe effek of maatreel van voedselsekerheid gehad in die intervensie groep. A verbetering van 8 tot 10 in die MAHFP median het plaasgevind (95%CI vir verandering [-2;0]). Die monster van ingesluit is in die huidige studie vir Lesotho, was hoofsaaklik van mans opgemaak. Omtrent helfde was getroud en minder as 20% het hoerskool voltooi of ‘n tersiere kwalifikasie. Hoe vlakke van armoede was opvallend met ‘n LPI van 2.5. tespyte van dit, was huishoudings verbasend nie so sleg af soos oorspronklik verwag nie. Selfs voor die intervensie, was die median MAHFP 11 in die kontrole groep en 10 in die intervensie groep, wat daarop aangedui het day huishoudings relatief goed doen met vlakke van voedselvoorsiening. Die median HDD telling voor die intervensie was 5 in die kontrole groep en 6 in die intervensie groep, dus het die huishoudings n matig tot hoog verskeidenheid in die dieet handhaaf. T.o.v. frekwensie van groenteinname, het n relatiewe hoe persentasie deelnemers rapporteer dat beide volwassenes en kinders gereeld groente geeet het. Die mededeelsaamheid wat beskryf word in Lesotho kon moontlik hiernatoe bygedra het. T.o.v. die impak wat die intervensie gemaak het, die MAHFP het dieselfde gebly (11) in die kontrole groep met die opvolg besoek en het met 1 punt verbeter in die intervensie groep. Median HDD telling het geen verandering in die kontrole of intervensie groep getoon nie. Die hoof uitkomste van hierdie studie was duidelik om die verwantskap tussen groente tuine en groenteinname te bepaal, maar huishoudings het geen verbetering gewys nie na die intervensie nie. Die monster van ingesluit is in die huidige studie vir Zimbabwe, was hoofsaaklik van vrouens opgemaak. Die mederheid was getroud en meer as 50% het hoerskool voltooi of ‘n tersiere kwalifikasie. Hoe vlakke van armoede was opvallend met ‘n LPI van 2.3. Tenspyte van dit, was huishoudings verbasend nie so sleg af soos oorspronklik verwag nie. Selfs voor die intervensie, was die median MAHFP 11 in die kontrole groep en 10 in die intervensie groep, wat daarop aangedui het day huishoudings relatief goed doen met vlakke van voedselvoorsiening. Die median HDD telling voor die intervensie was 6 in die kontrole groep en 7 in die intervensie groep, dus het die huishoudings n matig tot hoog verskeidenheid in die dieet handhaaf. T.o.v. frekwensie van groenteinname, het n hoe persentasie deelnemers rapporteer dat volwassenes gereeld groente geet het, al was dit minder as die volwassenes, het kinders ook gereeld groente geeet. T.o.v. die impak wat die intervensie gemaak het, die MAHFP het met 1 punt verbeter in die kontrole groep met die opvolg besoek dieselfde gebly in die intervensie groep. Median HDD telling het geen verandering in die kontrole of intervensie groep getoon nie. Die hoof uitkomste van hierdie studie was duidelik om die verwantskap tussen groente tuine en groenteinname te bepaal, maar omdat groenteinname reeds hoog was voor die intervensie – was daar geen betekenisvolle verbetering nie. Om af te sluit, het die impak van die huishoudelike greontetuin intervensie in elke land verskil. Hierdie kon aan verskillende vlakke in opvoeding, kultuur en omgewings faktore togeken word. Die verbetering wat wel opgemerk is, dui aan dat huishoudelike groentetuine die potensiaal het om beskikbaarheid van voedsel, vlak van verskeidenheid in die dieet en frekwensie van groenteinname te verbeter.
Dissertation (M.Sc. (Nutrition and Dietetics))--University of the Free State, 2018
Keywords: Food supply; Food insecurity; Malnutrition; Food supply -- Developing countries